Understanding Adherence in Patients With Coronary Heart Disease: Illness Representations and Readiness to Engage in Healthy Behaviours. (6th October 2013) - Platt, Ian; Green, Heather J; Jayasinghe, Rohan; Morrissey, Shirley A
<x xml:space="preserve">Abstract</x> In people with Coronary Heart Disease (CHD), poor adherence to medication, exercise, and dietary recommendations can compromise prognosis. This study investigated respective associations of the Commonsense Self‐Regulation Model (CSM), the Transtheoretical Model (TM), and trait affect with patients' self‐reported adherence to treatment. One hundred and forty‐two CHD outpatients completed the Illness Perceptions Questionnaire Revised, Self‐Efficacy, Stage of Change, Positive and Negative Affect Scale, and General Adherence Questionnaire. Stage of change and self‐efficacy were associated with self‐reported medication, diet, and exercise adherence. In comparison, the CSM accounted for a smaller proportion of variance in adherence. In hierarchical regression, the variance from CSM variables associated with exercise adherence was no longer significant when TM variables were in the equation. For dietary and medication adherence, in contrast, both emotional representations (CSM) and TM variables contributed independently to the regression equation. There was some evidence that trait affect moderated the association between the CSM variable of emotional representations and dietary adherence. Results suggest that the largest effects for improving adherence to medication, exercise, and dietary recommendations would occur by increasing readiness to change for exercise, increasing domain‐specific self‐efficacy, and decreasing negative emotions about CHD. Additional implications for research and practice are discussed.